EPIDERMAL GROWTH FACTOR RECEPTOR EXPRESSION IN A CASE OF FOCAL NODULAR GLIOSIS OF THE RETINA. Issue Volume 16:Issues 3(2022) (13th February 2020) - Tagami, Mizuki; Misawa, Norihiko; Noma-Ishikura, Saki; Honda, Satoshi; Kase, Satoru; Honda, Shigeru
Abstract : Expression of epidermal growth factor receptor in focal nodular gliosis of the retina. Abstract : Purpose: To describe the immunohistochemical profile in a case with focal nodular gliosis (FNG) of the retina. Methods: A 56-year-old female patient presented with vitreoretinal tractional syndrome with FNG of the retina. After resection of the retinal tumor tissue during the 25-G pars plana vitrectomy, immunohistochemistry using anti–epidermal growth factor receptor (EGFR), p-53, Ki67, glial fibrillary acid protein (GFAP), CD34, and vascular endothelial growth factor antibodies was performed in the excised tissue of the FNG of the retina. Results: Histopathological analysis of the tumor led to a diagnosis of FNG of the retina. Spindle cells of the tumor exhibited strong positive staining for glial fibrillary acid protein, and there was local staining for CD34 in the endothelial cells in the blood vessels. The epidermal growth factor receptor and vascular endothelial growth factor immunoreactivity were strongly observed in the endothelial cells. Conclusion: This study demonstrated epidermal growth factor receptor expression in eyes with FNG of the retina. Oncogenic epidermal growth factor receptor might trigger and amplify the expression and function of endothelial vascular endothelial growth factor.